Does superior caval vein pressure impact head growth in Fontan circulation?. (15th January 2016) - Trachsel, Tina; Balmer, Christian; Wåhlander, Håkan; Weber, Roland; Dave, Hitendu; Poretti, Andrea; Kretschmar, Oliver; Cavigelli-Brunner, Anna
Abstract: Background: Patients with bidirectional cavopulmonary anastomosis have unphysiologically high superior caval vein pressure as it equals pulmonary artery pressure. Elevated superior caval vein pressure may cause communicating hydrocephalus and macrocephaly. This study analysed whether there exists an association between head circumference and superior caval vein pressure in patients with single ventricle physiology. Methods: We carried out a retrospective analysis of infants undergoing Fontan completion at our institution from 2007 to 2013. Superior caval vein pressures were measured during routine catheterisation before bidirectional cavopulmonary anastomosis and Fontan completion as well as head circumference, adjusted to longitudinal age-dependent percentiles. Results: We included 74 infants in our study. Median ages at bidirectional cavopulmonary anastomosis and Fontan were 4.8 (1.6–12) and 27.9 (7–40.6) months, respectively. Head circumference showed significant growth from bidirectional cavopulmonary anastomosis until Fontan completion (7th (0–100th) versus 20th (0–100th) percentile). There was no correlation between superior caval vein pressure and head circumference before Fontan (R 2 =0.001). Children with lower differences in superior caval vein pressures between pre-bidirectional cavopulmonary anastomosis and pre-Fontan catheterisations showed increased growth of head circumference (R 2 =0.19). Conclusions: Patients with moderately elevated superior caval vein pressure associated with single ventricle physiology did not have a tendency to develop macrocephaly. There is no correlation between superior caval vein pressure before Fontan and head circumference, but between bidirectional cavopulmonary anastomosis and Fontan head circumference increases significantly. This may be explained by catch-up growth of head circumference in patients with more favourable haemodynamics and concomitant venous pressures in the lower range. Further studies with focus on high superior caval vein pressures are needed to exclude or prove a correlation.